Effects of 15-Year-Old Plantation on Soil Conditions, Spontaneous Vegetation, and the Trace Metal Content in Wood Products at Kipushi Tailings Dam - Mwanasomwe, Jacques Kilela; Langunu, Serge; Shutcha, Mylor Ngoy; Colinet, Gilles (Frontiers in Soil Science, 2022)
The revegetation of polluted lands has become the key strategy for remediation of derelict sites in the Copperbelt region because of their large size and the elevated concentration of trace metal in their soils. When these soils are recovered erosion through wind and water is reduced preventing migration of pollutants to other areas and lastly the land will provide goods and services instead of human exposure to trace metals. This study evaluated the effect of the reclamation with trees on the fertility and metal concentrations of soil, on the development of spontaneous vegetations and the concentration of metals in tree tissues. The Cu and Co concentration were higher in soil at the reclaimed area than on unreclamed area, which confirms the stabilization effect of pollutants in soil, with no significant improvement of fertility of the revegetated soil. Among the ten-tree species recorded, C. lusitanica and L. leucocephala need to be used with cautious in phytostabilisation, as the former had higher Zn and Cu accumulation in tissues (leaves and barks) and did not promote the facilitation of spontaneous vegetation, and the latter showed invasive characteristics. Bark tissues showed a high Zn, Cu and Co concentrations to most of the tree species tested, while wood had far lower content (mg kg−1 dry weight). This testifies that the metal concentrations in these organs might be airborne rather than soilborne. Concentration of Zn, Cu and Co was manifold higher in charcoal than in wood with no significant differences between charcoals regardless of the origin (tailing or unpolluted soil), therefore, the ashes from charcoals produced in this area (polluted or unpolluted lands) should be well monitored in term of metal content in comparison to the concentration limit standards in soil improvers, especially since the ash is always used by households as a soil amendment in gardens.